2012
DOI: 10.1007/s10517-012-1608-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile of the blood in mice with normal and abnormal heart rhythm

Abstract: Differences in the pools of 10 cytokine were found in blood samples from the caudal vein of mice with normal and abnormal heart rhythm. Both groups were albino mice bred by us and differing from mdx albino mice by the absence of mutation in muscular dystrophin gene. Mice with normal heart rhythm had low IL-17 content and elevated concentrations of proinflammatory cytokines IL-6 and IL-1α in comparison with the normal (according to published data). In mice with bradyarrhythmias, increased blood levels of IL-10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
4
8
0
Order By: Relevance
“…In both cases, at 18 weeks postirradiation, the two weeks of KL 4 treatment resulted in essentially baseline levels of both cytokines, while untreated control and vehicle-treated irradiated mice both clearly showed increase over baseline. The wide variability in levels is consistent with other reported studies (44). For IL-2, it is notable that only the irradiated untreated control and vehicle-treated mice had levels outside of normal reference ranges (44).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In both cases, at 18 weeks postirradiation, the two weeks of KL 4 treatment resulted in essentially baseline levels of both cytokines, while untreated control and vehicle-treated irradiated mice both clearly showed increase over baseline. The wide variability in levels is consistent with other reported studies (44). For IL-2, it is notable that only the irradiated untreated control and vehicle-treated mice had levels outside of normal reference ranges (44).…”
Section: Resultssupporting
confidence: 93%
“…The wide variability in levels is consistent with other reported studies (44). For IL-2, it is notable that only the irradiated untreated control and vehicle-treated mice had levels outside of normal reference ranges (44). In fact, despite the variability in the data, reduction in KL 4 vs. untreated control for IL-2 was statistically significant (19 ± 3 pg/ml vs. 35 ± 5, P = 0.02) and KL 4 treatment returned IL-2 levels to the normal range.…”
Section: Resultssupporting
confidence: 93%
“…17 Moreover, there were no clear patterns indicating that these minor differences were entirely treatment dependent. In all cases, differences were not dose-dependent and cytokine responses in phage treated mice were at times lower than in control mice.…”
Section: Discussionmentioning
confidence: 98%
“…Capoferri et al found in their studies that of the inflammatory markers, interleukin‐6 had the strongest correlation with relative bradycardia and other arrhythmias 7 . Interleukin‐6 is a significant inflammatory marker associated with the cytokine storm seen in COVID‐19 infection and has been reported to have direct impact on the sinoatrial node causing increased vagal tone and minimized heart rate variability ultimately leading to relative bradycardia 27‐29 . In addition to these hypotheses, as the disease course worsens arrhythmias are likely worsened by the hypoxia and multiorgan failure, resulting in electrolyte derangements and buildup of toxic metabolites 5,10 …”
Section: Mechanism Of Cardiac Involvementmentioning
confidence: 99%